Peningkatan Keterampilan Hidup Melalui Program Pengabdian Masyarakat Berbasis Inklusi - Gaeska, Nasywa Qalbi; Kamaly, Nurul; Afrijal (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Life skills are essential abilities that every individual needs to achieve independence and effective social integration. For children with special needs, the development of life skills is crucial. This community service program was conducted at Aceh Flexi School, an educational institution for children with special needs, to provide life skills training based on an inclusive approach.   Objective: The purpose of this service was to enhance the life skills of children with special needs through an inclusive and participatory learning approach. The service aimed to improve basic skills such as self-care, communication, and social interaction, while providing hands-on practice using media such as animated videos, origami, and concrete objects.   Method: This public service was conducted by the community service team from the Government Science Program, Syiah Kuala University, on December 5, 2024, involving 20 children aged 6–12 years old. The service utilized multimedia tools such as animated videos, origami, and concrete objects to engage children in interactive learning. The activities were designed to be participatory, with direct involvement from teachers and parents.   Result: The results showed significant improvement in the children's ability to perform basic life skills such as self-care, communication, and motor coordination. Most children were actively engaged in the learning process, demonstrating increased independence and social interaction during the activities. Positive feedback from teachers and parents indicated that the approach was highly effective in supporting the children's development.   Conclusion: The community service successfully contributed to enhancing the life skills of children with special needs at Aceh Flexi School. The use of inclusive and multisensory learning methods proved to be an effective strategy. Future initiatives should focus on sustainability through continuous support and collaboration with educational institutions and communities to further improve the skills of children with special needs.